Aktivitas Ligninolitik Beberapa Jamur Aphyllophorales dan Kemampuannya Mendegradasi Lignin pada Lindi Hitam - Atria Martina; Tetty Marta Linda; Delita Zul; Nila Veronika; Ratna Jelita (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2015)
Fourteen local isolate Aphyllophorales fungi were screened their ligninolytic activity. The isolate with highest ligninolytic activity was tested it capability to degrade kraft blackliquor lignin. The biodegradability of black liquor is low because the presence of lignin and lignin derivative in the wastewater. These fungal were screened for ligninolytic activity by decolorization on solid mediacontaining RBBR dye. The ability of the fungal strains to biodegrade kraft black liquor lignin was performed by submerged fermentation condition with agitation and incubation time as treatment. The solid culture result in 3 isolates had ligninolytic activity and Ganoderma sp.BTA1 gave the highest ligninolytic. Agitation and incubation time influenced ligninbiodegradation of blackliquor significantly. Optimum condition for lignin biodegradation was at 200 rpm during 25 days with lignin reduction was 45,786%.